Rhodococcus empyema in a heart transplant patient. Issue 1 (21st January 2014) - Rose, Richard; Nord, John; Lanspa, Michael
Abstract R hodococcus equi is a rare cause of pneumonia and empyema almost exclusively occurring in immunocompromised patients. Most people who become infected have direct exposure to livestock. We present a case where the exposure was presumed to be through a family member in close contact with horses. Our case describes an infection in a heart transplant patient that was initially identified as a probable intra‐abdominal infection and later reidentified as Rhodococcus equi empyema, and was treated with surgery and prolonged antibiotics.